2008
DOI: 10.3174/ajnr.a1354
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Characteristics and Neuropathology of the Spinal Cord in Adult-Onset Autosomal Dominant Leukodystrophy with Autonomic Symptoms

Abstract: BACKGROUND AND PURPOSE: MR imaging findings in adult-onset autosomal dominant leukodystrophy (ADLD) with autonomic symptoms have been described in the brain, but no descriptions of MR imaging findings in the spinal cord have been published. Here, we describe MR imaging findings in the spinal cord in adult-onset ADLD with autonomic symptoms and histopathologic investigations of the spinal cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 48 publications
5
35
0
1
Order By: Relevance
“…Tremor, previously reported in LMNB1 ‐related ADLD,2, 7 was present in less than half of the patients and caused major complaint in 1 patient. We found no signs of polyneuropathy, confirming earlier reports 2, 3, 4, 5, 24. A new observation in this follow‐up study is that sensory impairment started in the distal part of the legs and ascended over time to the thoracic level, consistent with myelopathy, and development of flaccid paralysis of the lower limbs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Tremor, previously reported in LMNB1 ‐related ADLD,2, 7 was present in less than half of the patients and caused major complaint in 1 patient. We found no signs of polyneuropathy, confirming earlier reports 2, 3, 4, 5, 24. A new observation in this follow‐up study is that sensory impairment started in the distal part of the legs and ascended over time to the thoracic level, consistent with myelopathy, and development of flaccid paralysis of the lower limbs.…”
Section: Discussionsupporting
confidence: 91%
“…This follow‐up study gives a strong indication that spinal cord involvement is clinically significant in this type of leukodystrophy and may also, at least partly, explain the autonomic dysfunction. Previous histopathological studies have verified involvement of the spinal cord in a patient already at 3 years after onset of symptoms5 and more‐severe changes in a patient with longer disease duration 24. In our study, clinical assessment, radiological findings, and neurophysiological examinations indicate myelopathy.…”
Section: Discussionsupporting
confidence: 74%
“…Spinal atrophy has been observed in groups of individuals with pathologies such as autosomal dominant leukodystrophy, amyotrophic lateral sclerosis and hereditary paraplegia. [5][6][7] Good correlation between spinal cord area (SCA) and a number of global clinical scores has also been found in several studies of patients with multiple sclerosis in cross-sectional as well as longitudinal settings. 8 It is not known whether a similar quantitative relation between spinal cord atrophy and the extent of disability is found in individuals with SCI.…”
Section: Introductionmentioning
confidence: 94%
“…Both exhibited a vacuolar degenerative phenotype primarily involving the white matter tracts with a preservation of oligodendrocytes. 20,21 This suggested that the over expression of lamin B1 is not lethal to oligodendrocytes and that the demyelination is not the result of oligodendrocyte loss. Recent reports have linked lamin b1 to pathways of cellular proliferation and senescence.…”
mentioning
confidence: 99%
“…While patient brain sections exhibited a modest degree of reactive gliosis, no astrocytic proliferation was observed, although the astrocytes in affected regions were found to have abnormal and shortened processes. 20,21 It is unclear whether these differences represent species-specific responses to lamin B1 overexpression. However, it is important to remember that ADLD has a relatively slow disease progression with death occurring at least a 10-20 y after the onset of symptoms.…”
mentioning
confidence: 99%